2006
DOI: 10.1002/ajmg.a.31520
|View full text |Cite
|
Sign up to set email alerts
|

Clinical‐etiologic correlation in children with Prader‐Willi syndrome (PWS): An interdisciplinary study

Abstract: Prader-Willi syndrome (PWS) is a multisystemic disorder caused by the loss of expression of paternally transcribed genes within chromosome 15q11-q13. Most cases are due to paternal deletion of this region; the remaining cases result from maternal uniparental disomy (UPD) and imprinting defects. To better understand the phenotypic variability of PWS, a genotype-phenotype correlation study was performed in 91 children with PWS. Patients were diagnosed by Southern Blot Methylation assay and genetic subtypes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…Genotype-phenotype analyses of PWS and AS patients have revealed that many genes throughout 15q11-13 contribute to the clinical manifestations of patients (Lossie et al 2001; Torrado et al 2007). Additionally, as maternally derived 15q11-13 duplications often lead to autism-spectrum disorder, the two maternally expressed imprinted genes ATP10A and UBE3A are prime candidate genes for the 15q11-13 associated autism phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype-phenotype analyses of PWS and AS patients have revealed that many genes throughout 15q11-13 contribute to the clinical manifestations of patients (Lossie et al 2001; Torrado et al 2007). Additionally, as maternally derived 15q11-13 duplications often lead to autism-spectrum disorder, the two maternally expressed imprinted genes ATP10A and UBE3A are prime candidate genes for the 15q11-13 associated autism phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In our overall sample 73% of the patients had deletion of chromosome 15 and 27% of the patients had uniparental disomy. The genetic picture was not related to the QoL.…”
Section: Relationship Between Qol Questionnaires' Scores and Genetic mentioning
confidence: 98%
“…125 In most studies, those with UPD have a somewhat higher verbal IQ and milder behavior problems. 19,126,127 However, psychosis 128 and autism spectrum disorders 129,130 occur with significantly greater frequency among those with UPD. Individuals with the slightly larger, type 1 deletions (BP1-BP3) have been reported…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%